The execution of the resolution by which finishes the economic-administrative procedure and its consequences (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2024)
This paper analyzes, in light of the recent jurisprudence issued by our courts of justice (and, in particular, taking into account the recent pronouncements issued by the Supreme Court), the different issues and situations that may arise when it comes to proceed to execute the Resolution issued by an Economic-Administrative Court, once the administrative review procedure is completed.
Keywords: Economic-administrative procedure; Resolution; execution act; appeal; retroaction of actions; liquidation; annulment